Insight Into the Molecular Mechanism of Podophyllotoxin Derivatives as Anticancer Drugs - Fan, Hua-yang; Zhu, Zhuo-li; Xian, Hong-chun; Wang, Hao-fan; Chen, Bing-jun; Tang, Ya-Jie; Tang, Ya-ling; Liang, Xin-hua (Frontiers in Cell and Developmental Biology, 2021)
Podophyllotoxin (PTOX) is a biologically active compound derived from the podophyllum plant, and both it and its derivatives possess excellent antitumor activity. The PTOX derivatives etoposide (VP-16) and teniposide (VM-26) have been approved by the U.S. Food and Drug Administration (FDA) for the cancer treatment, but are far from perfect. Hence, numerous PTOX derivatives have been developed to address the major limitations of PTOX, such as systemic toxicity, drug resistance and low bioavailability. Regarding their anticancer mechanism, extensive studies have revealed that PTOX derivatives can induce cell cycle G2/M arrest and DNA/RNA breaks by targeting tubulin and topoisomerase II, respectively. However, few studies are dedicated to exploring the interactions between PTOX derivatives and downstream cancer-related signaling pathways, which is reasonably important for gaining insight into the role of PTOX. This review provides a comprehensive analysis of the role of PTOX derivatives in the biological behavior of tumors and potential molecular signaling pathways, aiming to help researchers design and develop better PTOX derivatives.